Constructions with ‘take’ in Latgalian: The limits of diachrony - Nau, Nicole (Stellenbosch Papers in Linguistics Plus, 2022)
A collection of Latgalian oral folktales published in 1895 shows a great frequency of multi-verb constructions with a modifying verb ‘take’, including Serial Verb Constructions. These constructions are not found in Old Latgalian written texts, while in modern writing, only one type is attested: pseudo-coordination. Although the documentation of Latgalian spans almost three centuries, it is not possible to show grammaticalization paths of multi-verb constructions, as these are register-specific.